Interventions in the Pampas calden forest: regeneration of plant communities after disturbance (Semiárida, 2025)
Shrub encroachment in the Caldenal forests of central Argentina reduces forage productivity, biodiversity, and system accessibility, leading to closed physiognomies locally known as “fachinales.” To counteract this process, different management practices have been implemented, though their effects vary depending on disturbance intensity and time since intervention. This study aimed to evaluate the effects of mechanical treatments and prescribed burning on the structure and composition of a Calden (Neltuma caldenia) forest in La Pampa, Argentina. Seven treatments were established: control (T), burning (Q), roller-chopping (R), roller-chopping+burning (R+Q), shredding (Tr), roller-chopping+shredding (R+Tr), and bulldozing (Tp). Vegetation surveys were conducted in 2022 using 84 plots. Species richness, diversity, evenness, vegetation strata, litter, bare soil, exotic and forage species were recorded. ANOVA and multivariate analyses (cluster and SIMPER) were applied. Richness was highest in T, but evenness increased under Tp and R+Tr. Bulldozing produced the greatest canopy opening and favored forage grasses, while R and Q maintained closed communities dominated by non-forage species. Exotic species cover increased under Tp and at community edges. Multivariate analyses confirmed the disturbance-intensity gradient and identified diagnostic species, such as N. caldenia in closed stands and Poa ligularis and Piptochaetium napostaense in more open areas. Results indicate that intense interventions are necessary to initiate restoration but require follow-up management and adaptive strategies. Combining practices, adjusted to degradation state and management goals, emerges as the most suitable approach to recover the ecological and productive functionality of the Caldenal forest.
Keywords: calden forests; restoration; forage quality; exotic vegetation; adaptive management